Tristan & Isolde [videorecording (DVD)] - Reynolds, Kevin, 1952-; Franco, James, 1978-; Myles, Sophia, 1980-; Sewell, Rufus, 1967- (20th Century Fox Home Entertainment, 2006)
A young Tristan sees his parents killed by the tyrannical Irish, who ruled over a fractured Britain after the Roman occupation. Tristan is taken in by Marke, who rules one of the British tribes. Tristan grows up to be a young prince and a mighty warrior. He's believed slain in battle and given a royal funeral on a burning boat set out to sea. But the fire goes out and Tristan washes ashore on Ireland, where Isolde, the daughter of the Irish king, nurses him back to health. The two fall in love and set in motion a tragic tale that's lasted for centuries.